1999
DOI: 10.1016/s0008-6363(99)00160-1
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase expression and role during cardiomyogenesis

Abstract: Both, iNOS and eNOS isoforms are prominently expressed during early stages of cardiomyogenesis. Around E14.5 NOS expression starts to decline. Moreover, the NO-generation is required for cardiomyogenesis since NOS inhibitors prevent the maturation of terminally differentiated cardiomyocytes using the ES cell system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
88
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(94 citation statements)
references
References 26 publications
6
88
0
Order By: Relevance
“…Mujoo et al also demonstrated an increase of sGC subunits during the course of differentiation of human ESCs for 14 days, but the authors reported a progressive decrease in sGCβ 2 mRNA from day 0 to day 14 [ 10 ]. These observed differences may be attributed to differences in the ESC species and strains, or l -nitroarginine, the number of EB-derived cardiomyocytes is not affected, but fi brillogenesis in the cardiomyocytes is reduced [ 32 ]. This effect is mimicked by ODQ (an antagonist of soluble guanylate cyclase).…”
Section: Discussionmentioning
confidence: 96%
“…Mujoo et al also demonstrated an increase of sGC subunits during the course of differentiation of human ESCs for 14 days, but the authors reported a progressive decrease in sGCβ 2 mRNA from day 0 to day 14 [ 10 ]. These observed differences may be attributed to differences in the ESC species and strains, or l -nitroarginine, the number of EB-derived cardiomyocytes is not affected, but fi brillogenesis in the cardiomyocytes is reduced [ 32 ]. This effect is mimicked by ODQ (an antagonist of soluble guanylate cyclase).…”
Section: Discussionmentioning
confidence: 96%
“…Immunoreactivity for eNOS or nNOS was faint in non-diabetic and diabetic groups. Although it has been reported that E9.5 embryos display eNOS expression in the murine heart and limb skeletal myocytes [33,34], these studies did not analyse eNOS expression in the neural tube. It is well known that the expression of iNos mRNA is regulated by nuclear factor kappa B (NFκB) activated by proinflammatory cytokines such as TNF-α and IFN-γ.…”
Section: Discussionmentioning
confidence: 99%
“…Failure of NCC migration results in CVMs, particularly those involving malformations of the great vessels and cardiac outflow tract defects, such as truncus arteriosus [44]. Bloch et al reported that iNOS expression starts at an early stage (E8.5) of murine/rat heart development [33]. Several lines of evidence show that iNOS expression is induced by proinflammatory cytokines, such as TNF-α and IL-1β, and that the resulting increase in nitric oxide generation causes cardiac cell degeneration and apoptosis [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…10 Mice deficient in eNOS also possess limb reduction defects, possibly due to vascular insufficiency. These limb abnormalities were seen in Ϸ10% of the null animals, and they resemble the limb reduction defects seen in patients with Holt-Oram Syndrome.…”
Section: Lee Et Al Bicuspid Aortic Valve In Enos Knockout Mice 2347mentioning
confidence: 99%